PEMBELAJARAN SASTRA ANAK BERBASIS KEARIFAN LOKAL INDONESIA: TINJAUAN LITERATUR SISTEMATIS - Ibda, Hamidulloh; Wijayanti, Dian Marta (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
This article presents a systematic review of literature related to learning children’s literature based on Indonesian local wisdom. Further research is needed to determine what to do, how, and why learning children’s literature should be based on Indonesian local wisdom. Writing this article was assisted by the Publish or Perish 7, Mendeley, VOSviewer, and NVIVO 12 Plus applications. The search for articles in the Google Scholar database is limited to the last 3 years, namely 2020-2022. From the search results in the Publish or Perish 7 application, there are 2361 articles on Google Scholar, then articles are selected according to compatible themes into 40 selected articles. The findings of the themes/topics are learning children’s literature, children’s literature, local wisdom, children’s reading, digital teaching materials, reading, folklore, poetry, moral values, local wisdom, literacy, oral literature, folklore, drama text, cultural identity, children’s stories, children’s literature teaching, and others. Of these 40 articles, they were analyzed according to the topics determined through the NVIVO 12 Plus application and the results described according to research questions. Learning children's literature based on Indonesian local wisdom is determined by various aspects. Many studies reveal the learning of local wisdom-based children's literature through various types, such as oral literature. Educators must understand conceptually and implementatively so that the nature of children's literature does not simply become a dead text but is truly enjoyable for children. This article contributes to subsequent research and becomes a study for the theme of learning children’s literature based on Indonesian local wisdom.